Discovery of WINERED-HVS1: A Metal-rich Hypervelocity Star Candidate Ejected from the Galactic Center - Kohei Hattori; Daisuke Taniguchi; Takuji Tsujimoto; Noriyuki Matsunaga; Hiroaki Sameshima; Scarlet S. Elgueta; Shogo Otsubo (The Astrophysical Journal)
We report the discovery of a metal-rich red-giant star, WINERED-HVS1, which is a candidate for a hypervelocity star (HVS). Its past trajectory suggests that this star may have been ejected by the Galactic supermassive black hole (SMBH; Sgr A*), with a modest ejection velocity of at least 500 km s ^−1 . Since WINERED-HVS1 is gravitationally bound to the Milky Way and is not necessarily young, it is not an unambiguous HVS candidate from a kinematic perspective, unlike the previously confirmed A-type main-sequence HVS known as S5-HVS1. Therefore, the chemical characterization of this star is essential for understanding its origin. Through a spectroscopic follow-up observation with Magellan/WINERED, we determined its metallicity $[{\rm{Fe}}/{\rm{H}}]=-0.14{7}_{-0.045}^{+0.046}$ , as well as the abundances of Na, Mg, Si, S, K, Ca, Ti, Cr, Ni, and Sr. The high-metallicity value suggests that this star was ejected from the Galactic center and is unlikely to be a halo star with a radial orbit. The abundance pattern of this star—including the patterns of [ α /Fe], [Mg/Fe], [Si/Mg], and [Ca/Mg]—is consistent with that of the nuclear star cluster surrounding the SMBH, further supporting our view. This discovery opens a new window to look through the Galactic center environment without the hindrance of dust extinction, by using the HVSs moving in the halo region where dust extinction is minimal.